2015
DOI: 10.1016/j.ahj.2015.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Ticagrelor versus clopidogrel in Asian patients with acute coronary syndrome: A retrospective analysis from the Platelet Inhibition and Patient Outcomes (PLATO) Trial

Abstract: We observed consistency of effects in Asian patients receiving ticagrelor and clopidogrel in the PLATO study. The relatively modest number of Asian patients in this analysis supports further investigation of larger cohorts to confirm our observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
81
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 25 publications
6
81
2
Order By: Relevance
“…It was similar to the study from Lindholm et al, (2014) in patients with NSTE-ACS; the primary end point was better on ticagrelor compared to clopidogrel (10.0% vs. 12.3%, HR 0.83, CI 95% 0, 74-.93) [30]. However, this study differed from other studies such as Steg et al, (2010) and Kang et al, (2015) [31,32]. According to Steg et al, (2010) ticagrelor compared to clopidogrel therapy did not differ significantly in preventing the primary endpoint in patients with STEMI with PCI HR 0.87 (95% CI, 0.75 to 1.01, p = 0.07) [31], while study from Kang et al, (2015) showed us that ticagrelor therapy was not significantly different than clopidogrel in preventing the primary endpoint in patients who have CHD in Asia population [32].…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…It was similar to the study from Lindholm et al, (2014) in patients with NSTE-ACS; the primary end point was better on ticagrelor compared to clopidogrel (10.0% vs. 12.3%, HR 0.83, CI 95% 0, 74-.93) [30]. However, this study differed from other studies such as Steg et al, (2010) and Kang et al, (2015) [31,32]. According to Steg et al, (2010) ticagrelor compared to clopidogrel therapy did not differ significantly in preventing the primary endpoint in patients with STEMI with PCI HR 0.87 (95% CI, 0.75 to 1.01, p = 0.07) [31], while study from Kang et al, (2015) showed us that ticagrelor therapy was not significantly different than clopidogrel in preventing the primary endpoint in patients who have CHD in Asia population [32].…”
Section: Discussioncontrasting
confidence: 52%
“…However, this study differed from other studies such as Steg et al, (2010) and Kang et al, (2015) [31,32]. According to Steg et al, (2010) ticagrelor compared to clopidogrel therapy did not differ significantly in preventing the primary endpoint in patients with STEMI with PCI HR 0.87 (95% CI, 0.75 to 1.01, p = 0.07) [31], while study from Kang et al, (2015) showed us that ticagrelor therapy was not significantly different than clopidogrel in preventing the primary endpoint in patients who have CHD in Asia population [32]. This could be due to differences in the characteristics of the subject, method, sample size, type of disease and some possible causes that could affect the results.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Using the cohort from the PLATO trial, there was no difference in bleeding events found in Asian subjects treated with ticagrelor compared to clopidogrel when compared to the rest of the study cohort [76]. The authors did note the relatively small Asian cohort relative to the entire study population.…”
Section: Platelet Aggregationmentioning
confidence: 99%